THE ANALYSIS OF PORK AND OFFALS HEALTH PRODUCTED IN DENPASAR SLAUGHTER HOUSE - Swacita, Ida Bagus Ngurah; Resmihariningsih, Ida Ayu; Suada, I Ketut; Budiasa, Ketut (Buletin Veteriner Udayana, 2021)
Food safety aspects of animal origin need special attention because the new diseases that attack humans are almost 75% caused by infectious agents that come from animals or animal products. The purpose of this study was to analyze the health of pork and offals (innards) by slaughterhouse production, which potentially transmits zoonotic disease in humans. This research used a qualitative explorative survey method that analyzed the health of pig meat and offals inspected by inspection, palpation, and incision based on sex difference (male and female) and animal age (young and adult) with total samples examined each of 100 samples. The results of this study indicate that pork is examined in Pesanggaran abattoir all healthy, pulmonary organs show necrosis 15% (9% adult females/AF and 6% adult males/AM), 30% pneumonia (22% AF and 8% AM), hemorrhage and pneumonia 5% (4% AF and 1% AM), in the heart organ 13% showed hypertrophy/hyperplasia (7% AF and 6% AM), and 1% of the liver (AM) had cysticercosis. It can be concluded that pork slaughterhouse production in Pesanggaran is all healthy and only a small part of the offals (5-30%) shows abnormalities that have the potential to transmit zoonotic diseases to humans.